2018
DOI: 10.1177/1059840518761792
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Perceptions of School Safety

Abstract: This study examined the relationship of students' perceptions of school safety and school avoidance related to feeling unsafe with predictor variables: bullying victimization, student/teacher/parent/administration relations, rule clarity and consistency, school physical environment (negative and positive), and student's belongingness. In a public high school sample ( n = 585), 24.7% of students felt unsafe and 14.4% avoided school due to feeling unsafe during the past month. Being female and experiencing bully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 46 publications
(61 reference statements)
1
21
0
6
Order By: Relevance
“…Positive relationships with teachers and peers can nurture a learning climate that meets adolescents’ developmental needs 1. Consistent findings concluded that higher level of teacher support was a strong predictor for better academic performance, emotional health, safety, and low rates of absences from schools among adolescents 6,9…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Positive relationships with teachers and peers can nurture a learning climate that meets adolescents’ developmental needs 1. Consistent findings concluded that higher level of teacher support was a strong predictor for better academic performance, emotional health, safety, and low rates of absences from schools among adolescents 6,9…”
Section: Discussionmentioning
confidence: 87%
“…Such studies had linked a negative perception of school climate with lower emotional wellbeing and greater tobacco consumption by adolescents 29. Other studies showed that unsafe schools climate is a strong predictor of high rates of dropout and truancy, low academic achievement, and drug and alcohol use among adolescents 5,9,24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In provision of school health services, school nurses can incorporate school district MTSS to provide traumaresponsive mental health policies and practices in schoolwide mental health promotion initiatives (Hoover, 2019). School nurses can also reach out to students who feel disconnected and share options that may meet their interests (Williams et al, 2018).…”
Section: Vulnerabilities To Student Belonging and School Connectedness Traumamentioning
confidence: 99%
“…Likewise with research conducted by Lumpkin, J., Hope, & Lutfi (2014), who found that the quality of school buildings and their supporting facilities affected student learning achievement. That is because students who feel happy with the look of the school will be proud of the school and have a sense of ownership of the school so they will be happy to go to school (Williams et al, 2018).…”
Section: Facilities and Infrastructure Factorsmentioning
confidence: 99%